Outcomes of severe malaria and its clinical features in Gabonese children - Voloc, Alexandru; Kuissi Kamgaing, Eliane; Ategbo, Simon; Djoba Siawaya, Joel Fleury (Frontiers in Tropical Diseases, 2022)
Background Malaria remains one of the deadliest diseases in the tropic. Its severe form represents a major public health concern in sub-Saharan Africa. The study aimed to describe and analyze clinical features and outcomes of severe malaria in children from Libreville. Methods Medical records (March 2018- to December 2019) from the emergency ward of the “Mother and Child University Hospital” were analyzed. Children hospitalized for malaria who met one or more criteria of the severe form rating according to the WHO guideline were included in the study. Results One hundred thirty-four children (134) children were included in the study. All children were anemic with 44% of children showing severe anemia. Thirty-three percent (33%) of admitted children were comatose or agonizing. The most frequent form of severe malaria was cerebral malaria with 101 cases (75.4%). The death rate was 18.6% (25/134). Twenty-one (21) children (84% of the deceased) died within the first 48 hours of hospitalization. In the subgroup of the deceased children, hepatomegaly was significantly more frequent (88%) than in the subgroup of those who survived (2.8%) (χ2 = 97.38; p<0.0001); Leukocytosis was more pronounced in the subgroup of the children under one year p<0.0001). Deep acidotic breathing was more frequent in cerebral malaria (χ2 = 5.4; p = 0.02). Conclusions Data revealed a high malaria-associated fatality rate. Cerebral malaria was the most frequent severe form of malaria. The relatively high frequency of comatose and/or agonizing children on admission raises the question of parents’ awareness and poor initial assessment of children’s clinical state.